Coordinated optimization scheduling operation of integrated energy system considering demand response and carbon trading mechanism. (May 2023) - Yang, Peihong; Jiang, Hui; Liu, Chunming; Kang, Lan; Wang, Chunling
Highlights: A novel IES coordinated optimization scheduling operation model based on CCHP, carbon capture, IDR and ladder-type carbon trading mechanism is constructed. A novel DR scheme considering cooling, heating, and electricity load satisfaction is proposed, and its impact on demand-side load is analyzed in-depth. A carbon allowance mechanism in line with the operating characteristics of IES is proposed, and a ladder-type carbon trading cost model is constructed to reduce system carbon emissions and achieve low-carbon operation of IES economy. Abstract: The low-carbon economy operation of the integrated energy system can be realized by introducing the demand response and carbon trading mechanism into the optimal scheduling of the integrated energy system. In this paper, an optimal scheduling model based on CCHP and carbon capture device is proposed, which takes into account the demand response of cooling, heating and electricity load and ladder-type carbon trading mechanism. Firstly, a multi-energy and multi-type demand response model based on time-of-use electricity price and incentive mechanism is established, and user satisfaction is used to evaluate it. Then, a carbon trading model of integrated energy system is established considering the actual carbon emissions of the system and the ladder-type carbon trading mechanism. Finally, taking the minimum sum of energy purchase cost, maintenance cost, carbon emission cost and compensation cost as the objective function, combined with the operation constraints of multi-energy flow of integrated energy system, an optimal scheduling model which takes into account both low-carbon and economy is constructed, and the problem is transformed into a mixed integer linear problem and solved by CPLEX. By setting up four scenarios for example analysis, the results show that the system total cost of the ladder-type carbon trading is decreased by 5.9% compared with the traditional carbon trading, and on the basis, the system total operating cost is decreased by 3.1% after considering the user-side DR. The simulation results further show that the introduction of DR and ladder-type carbon trading mechanism can flexibly transfer load, reduce gas purchase and reduce system carbon emissions, which has significant application value.